Scaling-up Health-Arts Programmes: the largest study in the world bringing arts-based mental health interventions into a national health service. (February 2021) - Estevao, Carolina; Fancourt, Daisy; Dazzan, Paola; Chaudhuri, K. Ray; Sevdalis, Nick; Woods, Anthony; Crane, Nikki; Bind, Rebecca; Sawyer, Kristi; Rebecchini, Lavinia; Hazelgrove, Katie; Manoharan, Manonmani; et al.
Summary: The Scaling-up Health-Arts Programme: Implementation and Effectiveness Research (SHAPER) project is the world's largest hybrid study on the impact of the arts on mental health embedded into a national healthcare system. This programme, funded by the Wellcome Trust, aims to study the impact and the scalability of the arts as an intervention for mental health. The programme will be delivered by a team of clinicians, research scientists, charities, artists, patients and healthcare professionals in the UK's National Health Service (NHS) and the community, spanning academia, the NHS and the charity sector. SHAPER consists of three studies – Melodies for Mums, Dance for Parkinson's, and Stroke Odysseys – which will recruit over 800 participants, deliver the interventions and draw conclusions on their clinical impact, implementation effectiveness and cost-effectiveness. We hope that this work will inspire organisations and commissioners in the NHS and around the world to expand the remit of social prescribing to include evidence-based arts interventions.